Lipoma of the right atrium - Silveira,Wilson Luiz da (2001)
The patient is a 54-year-old asymptomatic male with a tumor in the right atrium that was diagnosed on transesophageal echocardiography and confirmed as a lipoma of the right atrium on computerized tomography. The patient underwent surgical repair with extracorporeal circulation. The tumor was resected, and its base of implantation in the atrium was repaired with a flap of bovine pericardium. The diagnosis of lipoma was confirmed on histopathological examination. Locating of the tumor with the aid of transesophageal echocardiography was very useful in the strategy of cannulation of the venae cava for installation of the circuit of extracorporeal circulation. The patient had a good postoperative evolution.